THE CORRELATION OF CHEMICAL EXPOSURE AND PERSONAL HYGIENE WITH IRRITANT CONTACT DERMATITIS AMONG WORKERS IN THE PRODUCTION WORKER - Rosanti, Eka; Rudyarti, Edwina; Diwa, Mochammad Azel Putra Sunda (Journal of Vocational Health Studies, 2018)
Background: The production process at PT. X using oxalic acid as a mixture of Gum Rosin and Turpentine. Oxalic acid is corrosive and toxic and readily oxidized by water and oxygen that can cause irritation, rashes, burns, and damage to the skin and can cause irritant contact dermatitis. Irritant contact dermatitis cases reached 85% in the workplace. This is caused by direct exposure to chemicals, lack of attention to hygiene, sanitation and the lack of use of personal protective equipment. Purpose: This study aimed to study the correlation of chemicals exposure and personal hygiene with the incidence of irritant contact dermatitis on production workers of PT. X. Method: This was a quantitative research with cross-sectional approach. The population was 35 workes of PT. X. The sampling technique used total sampling, while data analysis by using  Pearson Correlation test. Result: The test results showed that there was a significant correlation between the exposure of the chemical with the occurrence of irritant contact dermatitis with p value = 0.047, whereas the correlation between personal hygiene with the incidence of irritant contact dermatitis with p value = 0.202 (insignificant). Conclusion: the exposure of chemicals significantly correlate with the occurence of contact dermatitis among the workers, while the personal hygiene had no correlation with the occurrence of irritant contact dermatitis of workers.